2010
DOI: 10.1007/s00424-009-0781-9
|View full text |Cite
|
Sign up to set email alerts
|

Colonic potassium handling

Abstract: Homeostatic control of plasma K+ is a necessary physiological function. The daily dietary K+ intake of approximately 100 mmol is excreted predominantly by the distal tubules of the kidney. About 10% of the ingested K+ is excreted via the intestine. K+ handling in both organs is specifically regulated by hormones and adapts readily to changes in dietary K+ intake, aldosterone and multiple local paracrine agonists. In chronic renal insufficiency, colonic K+ secretion is greatly enhanced and becomes an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 133 publications
1
61
0
1
Order By: Relevance
“…6,11,12 Previous studies revealed the importance of aldosterone for colonic K + adaptation, 3,54 and showed an upregulation of electrogenic Na + and K + transport and mRNA expression of BK channels and ENaC in the distal colon of mice on a high-K + diet. 11,13 Here, we confirmed that a K + diet induced activation of Na + reabsorption and K + secretion in the colon of AS +/+ mice. However, this adaptation of Na + and K + channel activity was completely absent in the colon of AS 2/2 mice.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…6,11,12 Previous studies revealed the importance of aldosterone for colonic K + adaptation, 3,54 and showed an upregulation of electrogenic Na + and K + transport and mRNA expression of BK channels and ENaC in the distal colon of mice on a high-K + diet. 11,13 Here, we confirmed that a K + diet induced activation of Na + reabsorption and K + secretion in the colon of AS +/+ mice. However, this adaptation of Na + and K + channel activity was completely absent in the colon of AS 2/2 mice.…”
Section: Discussionmentioning
confidence: 98%
“…6,11,12 We placed colonic mucosa from AS +/+ and AS mice ( Figure 7, A and C). However, in response to the 2% K + diet, K + and Na + channel activities rose significantly in the colonic mucosa of the AS +/+ mice only (Figure 7).…”
Section: Regulation Of Electrolyte Transport In the Late Distal Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Although systemic PHA-1 is normally also characterized by hyperkalemia, we did not find a shift in the potassium balance in the Scnn1a KO mice (Figures 4 and 5), which may be explained by differentially regulated and spatially separated electrogenic sodium absorption and potassium secretion. 31 …”
Section: Scnn1amentioning
confidence: 99%
“…BK channels have been implicated in a variety of physiological processes (Berkefeld et al 2010), which range from regulation of smooth muscle tone (Brayden and Nelson 1992) to modulation of hormone and neurotransmitter release (Waring and Turgeon 2009). Interestingly, BK channels are also involved in modulating K + transport in the mammalian kidney (Bailey et al 2006, Pulznick and Sansom 2006, Wang and Giebisch 2009, Holtzclaw et al 2010 and colon epithelium (Sorensen et al 2010).…”
Section: Introductionmentioning
confidence: 99%